2004
DOI: 10.1161/01.atv.0000143384.69170.2d
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow–Derived Monocyte Chemoattractant Protein-1 Receptor CCR2 Is Critical in Angiotensin II–Induced Acceleration of Atherosclerosis and Aneurysm Formation in Hypercholesterolemic Mice

Abstract: Abstract-Angiotensin II (Ang II) is implicated in atherogenesis by activating inflammatory responses in arterial wall cells.Ang II accelerates the atherosclerotic process in hyperlipidemic apoEϪ/Ϫ mice by recruiting and activating monocytes. Monocyte chemoattractant protein-1 (MCP-1) controls monocyte-mediated inflammation through its receptor, CCR2. The roles of leukocyte-derived CCR2 in the Ang II-induced acceleration of the atherosclerotic process, however, are not known. We hypothesized that deficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 28 publications
5
130
0
1
Order By: Relevance
“…Monocyte chemoattractant protein-1 is a key inflammatory mediator in atherosclerosis and is overexpressed in IA and subarachnoid hemorrhage after aneurysm rupture. 29 In experimental models, MCP-1 was upregulated in aneurysm walls, and MCP-1 knockout mice demonstrated a decreased expression of MMPs and inhibition of aneurysmal progression. 30 In both SMCs and endothelial cells, VCAM-1 is a potent mediator of inflammatory cell adhesion and found to be upregulated in both experimental aneurysm models 31 as well as in humans after aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte chemoattractant protein-1 is a key inflammatory mediator in atherosclerosis and is overexpressed in IA and subarachnoid hemorrhage after aneurysm rupture. 29 In experimental models, MCP-1 was upregulated in aneurysm walls, and MCP-1 knockout mice demonstrated a decreased expression of MMPs and inhibition of aneurysmal progression. 30 In both SMCs and endothelial cells, VCAM-1 is a potent mediator of inflammatory cell adhesion and found to be upregulated in both experimental aneurysm models 31 as well as in humans after aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent well designed study by Kanematsu et al (2011), macrophage-depleted mice were found to have a substantially lower risk of developing IA compared with control mice (10% versus 60%, respectively). In addition, two studies have investigated the role of monocyte chemoattractant protein 1 (MCP1), a seemingly important chemoattractant of macrophages in atherosclerosis and abdominal aortic aneurysms (Egashira, 2003;Ishibashi et al, 2004), reporting a lower incidence of IA and inflammatory findings in MCP1-knockout mice (Aoki et al, 2009b;Kanematsu et al, 2011). MCP1 expression in VSMC of IA was found to be mediated by Ets-1, a transcription factor involved in several vascular inflammatory pathways (Aoki et al, 2010).…”
Section: Intracranial Aneurysms and Inflammationmentioning
confidence: 99%
“…After 4 weeks on the experimental diets, all mice received angiotensin Ⅱ (1.9 mg/kg per day) for 4 weeks 22,24) . Angiotensin Ⅱ was dissolved in phosphate-buffered saline and loaded into miniosmotic pumps (Alzet, Cupertino, CA) according to the recommendations of the manufacturer.…”
Section: Experimental Protocolmentioning
confidence: 99%